The effect of feed fermentation by using (Synbiotic) on some of the productive indicators of broiler chickens - العسس عامر; زهير جبور (Latakia University Journal -Biological Sciences Series, 2022)
A trial was carried out to study the effect of including different levels of wet or fermented feed by using Synbiotic in the daily feed of broilers on some productivity indicators of broilers, 3000 one day-old chicks of commercial meat line(ROSS) were used in the trial. Then distributed to ten groups, each group containing 300 chicks with three replications: (A) negative witness, without addition to their feed or water, (B) positive control with Synbiotic to its dry daily Feed until the end of the experiment (W) 25% wet feed + 75% dry feed without symbiotic (W1) 50% wet feed + 50% dry feed without symbiotic (W2) 75% wet feed + 25% dry feed without symbiotic (W3) 100% wet feed until the end of the experiment (F) 25% fermented Feed by using symbiotic + 75% dry feed without symbiotic (F1) 50% Fermented feed by using symbiotic+50% dry feed without symbiotic (F2)75% Fermented feed by using symbiotic + 25%dry feed without symbiotic (F3) 100% Fermented feed by using symbiotic. the experiment continued until 43 days of age. The results of the study at the age of 36,43-d showed a significant increase (P < 0.05) of group F3 compared to A, and there were no significant differences with B, The improvement of (FCR) was related with an increase the level of fermentation and its deterioration with wet feeds. at the age of 36 The best weight was to group B, with high significant (P < 0.01) compared to W, A and a significant increase (p<0.05) compared to the rest of the groups, At the age of 43 the F3 group had the best weight and the negative control group had the lowest final weight. The results of the European Production Efficiency Factor on day 36 also showed a significant increase (P < 0.05) for B compared to W, W1, W2, W3, F, A and no significant differences compared to (F1, F2, F3), At the age of 43 the F3 group was the best and the lowest for W3. The results of the research showed the efficiency of adding the Synbiotic to dry feed until the age of 36 d, and the efficiency of feed fermentation in improving productivity indicators at old ages.